2001
DOI: 10.1046/j.1365-2982.2001.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in the small intestines of wildtype and W/WV mice

Abstract: Seven known genes were differentially expressed in wildtype and W/W(V) mice. COX7B (cytochrome c oxidase, subunit VIIb) and SORCIN (encoding multidrug-resistance complex, class 4) were suppressed in both fed and fasted W/W(V) mice. Expression of another five genes was increased in W/W(V) mice: ADA (adenosine deaminase), MDH1 (malate dehydrogenase), RPL-8 (ribosomal protein L8), SPTB2 (spectrin, nonerythroid, beta subunit), and p6-5 (encoding phosphorylcholine [PC] T-cell suppressor factor [TsF]). Differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…1B). These results are similar to those reported in previous studies (Malysz et al, 1996;Takayama et al, 2001Takayama et al, , 2002Nakagawa et al, 2005).…”
Section: Immunohistochemical Studiessupporting
confidence: 83%
See 1 more Smart Citation
“…1B). These results are similar to those reported in previous studies (Malysz et al, 1996;Takayama et al, 2001Takayama et al, , 2002Nakagawa et al, 2005).…”
Section: Immunohistochemical Studiessupporting
confidence: 83%
“…Furthermore, it has been reported that smooth muscle preparations of the small intestine (duodenum, jejunum or ileum) of W/W V mutant mice show a variety of electrical activities (Malysz et al, 1996), longitudinal cyclic contractions (Daniel et al, 2002) and distension-induced peristalsis . In the small intestine of W/W V mutant mice, while ICC-MY are absent, the ICC of the deep muscular plexus region (ICC-DMP) are present (Malysz et al, 1996;Takayama et al, 2001Takayama et al, , 2002. Recent studies reported the presence of synapse-like contacts between enteric nerve terminals and intramuscular ICC (ICC-IM) in the stomach, where ICC-MY have been shown to be the pacemaker ICC (Ward et al, 2000(Ward et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…We confirmed that there was no c-Kit positive immunoreactivity for ICC-MY in the ileum of W/W v DSS (-) mice, although there was for ICC-MY in the ileum of WT DSS (-) mice, as reported in previous studies (Malysz et al, 1996;Takayama et al, 2001;Nakagawa et al, 2005) (data not shown). There were no differences in the distribution of nNOS positive immunoreactive nerve fibers between WT DSS (-) mice and WT DSS (+) mice (n=2 each) in the ICC-DMP region of the circular smooth muscle (Fig.…”
Section: Immunohistochemical Studiessupporting
confidence: 78%
“…We pursued the hypothesis that such genes might show differential expression in the GI tracts of wild-type mice and W/W V mice. [3][4][5][6] To determine the differential expression, an extensive analysis was performed to examine gene expression in the fundus of wild-type and W/W V mice. We identified dozens of differentially expressed unannotated transcripts, whose sequences were available only as expressed sequence tags (ESTs).…”
Section: Conclusion Differential Gene Comparisons Between Control Amentioning
confidence: 99%